2010
DOI: 10.1111/j.1553-2712.2010.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Principles for Resident Remediation: Recommendations of the CORD Remediation Task Force

Abstract: Remediation of residents is a common problem and requires organized, goal-directed efforts to solve. The Council of Emergency Medicine Residency Directors (CORD) has created a task force to identify best practices for remediation and to develop guidelines for resident remediation. Faculty members of CORD volunteered to participate in periodic meetings, organized discussions and literature reviews to develop overall guidelines for resident remediation and in a collaborative authorship of this article identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 28 publications
1
72
0
1
Order By: Relevance
“…Poor performance can have confounding or contributing factors such as stress at home, substance abuse, cognitive issues related to language or processing issues, etc. 13 As noted later, the program director or CCC should not try to diagnose confounding problems but can help point the resident to resources to help him or her identify and treat any contributing factors. The remediation plan should only target and address the specific issue(s) identified, should have clearly defined goals with defined measures/assessments, a clearly defined and realistic timeline for achieving the goals, designated faculty or mentors (if necessary) to assist the resident, defined points along the timeline for the resident and program director to meet and assess progress to date, and clearly delineated consequences or next steps if the resident fails the remediation plan ( Table 1).…”
Section: Development and Monitoring Of The Remediation Planmentioning
confidence: 98%
See 2 more Smart Citations
“…Poor performance can have confounding or contributing factors such as stress at home, substance abuse, cognitive issues related to language or processing issues, etc. 13 As noted later, the program director or CCC should not try to diagnose confounding problems but can help point the resident to resources to help him or her identify and treat any contributing factors. The remediation plan should only target and address the specific issue(s) identified, should have clearly defined goals with defined measures/assessments, a clearly defined and realistic timeline for achieving the goals, designated faculty or mentors (if necessary) to assist the resident, defined points along the timeline for the resident and program director to meet and assess progress to date, and clearly delineated consequences or next steps if the resident fails the remediation plan ( Table 1).…”
Section: Development and Monitoring Of The Remediation Planmentioning
confidence: 98%
“…13,14 Remediation is often the first step before probation, which is usually followed by termination if the resident fails to improve. However, depending on the severity of the issue(s), a failed remediation could also end in dismissal or nonrenewal of contract if the resident fails to achieve the defined goals, and probation may be the first step rather than remediation.…”
Section: Development and Monitoring Of The Remediation Planmentioning
confidence: 99%
See 1 more Smart Citation
“…La littérature s'accorde à reconnaitre l'importance de mettre en oeuvre des processus de remédiations de telles difficultés [6][7][8][9] . On souligne notamment l'importance d'identifier les difficultés rapidement, de poser un diagnostic pédago-gique de ces difficultés, d'en identifier la source ou les causes, enfin de mettre en oeuvre un plan de remé-diation et de suivi, à la fois personnalisé et spécifique, des difficultés identifiées [8][9][10][11][12] .…”
Section: Introductionunclassified
“…The comprehensive reference list provided by Weizberg et al sits at just nine articles. A key reference is the excellent work by Katz et al, 2 which provides standardized definitions and a suggested guideline for the process.…”
mentioning
confidence: 99%